MODIFIED ACID FAST STAINING: A BETTER DIAGNOSTIC TOOL IN CHRONIC DIARRHOEA DUE TO CRYPTOSPORIDIOSIS - Mumtaz, Shahina; Ahmed, Jawad; Ali, Liaqat; Hussain, Hamid (Journal of Ayub Medical College Abbottabad, 2011)
Background: Cryptosporidium parvum is an emerging pathogen responsible for chronic diarrhoea in children and immuno-compromised individuals, especially AIDS patients. Currently, there is no effective therapeutic strategy for treating cryptosporidiosis, therefore control and supportive treatment of cryptosporidiosis depends upon rapid and accurate diagnosis of this infection. Methodology: A descriptive study was conducted in the Pathology Department of Khyber Medical College and Pathology Laboratory of Khyber Teaching Hospital over a period of one year March 2007-April 2008. A total of 200 stool samples were tested for the presence of C. parvum oocysts from children <5 years age suffering from diarrhoea for >5 days. Total and differential leukocyte count was determined to assess immune status of the patients. Modified Ziehl-Neelsen (Z-N) staining, a rapid, sensitive and easy test, was used successfully for the detection of C. parvum oocysts in stool specimen. Results: Cryptosporidium oocysts were found in 18 (9.0%) samples. Out of 18 positive cases, 13 (72.2%) children had lymphopenia hence their immune status was impaired. Infection was common in children between 1-24 months of age. Mean duration of diarrhoea was 11 months. Most of C. parvum infected children were consumers of well water (77.8%). Conclusion: Cryptosporidiosis, although a self-limiting disease, rarely investigated routinely, can become chronic and life threatening in immuno-compromised individuals. Majority of affected patients are immunecompromised. Modified Z-N is a sensitive and rapid method which can explore the gravity of this infection even further if used routinely and may control morbidity and mortality associated with this infection. Keywords: Chronic diarrhoea, modified Ziehl-Neelsen staining, immuno-comprised